The Challenges of Emergency Medical Services Response to Arasbaran Twin Earthquakes; a Content Analysis: Iranian EMS Response to Arasbaran Earthquakes - Pouraghaei, Mahboub; Babaie, Javad; Rad Saeed, Laleh (Archives of Academic Emergency Medicine, 2022)
Introduction: One of the most important concerns in responding to disasters is providing Basic Life Support (BLS) services. Considering the key role of Emergency Medical Services (EMS) in providing BLS, the purpose of this study is to investigate the experience of provincial EMS during their response to the Arasbaran twin earthquakes and its challenges in Iran. Methods: This study was conducted using a qualitative approach and the conventional content analysis method. Data were collected through Focused Group Discussions (FGD) and semi-structured in-depth interviews with purposively-selected EMS paramedics and officials in East Azerbaijan Province, Iran. To form the main categories, the interviews were encoded in three stages and the similar codes were placed under the same subcategories and merged. Results: A total of 26 EMS paramedics participated in the study. The codes extracted from the interviews, after three stages of reduction, were placed in the top ten categories, including the lack of preparedness and coordination, dead bodies’ management challenges, responders’ psychosocial support, deficiencies in supplies and ambulances, difficulty of access to rural areas, volunteer management, non-documentation of the experiences, communication challenges, recalling, and deploying of EMS responders. Conclusion: Timely response of the EMS and paramedics’ sense of responsibility for providing services were positive and successful points about the emergency response operations. The weaknesses of EMS should, therefore, be addressed through transferring of experiences and by planning and arranging training courses.